1984
DOI: 10.1111/j.1699-0463.1984.tb04372.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERNALIZATION IN VIVO OF CHOLERA TOXIN IN THE SMALL INTESTINAL EPITHELIUM OF THE RAT

Abstract: Internalization in vivo of cholera toxin in the small intestinal epithelium of the rat. Acta path. microbiol. immunol. s a n d . Sect. A. 92: 15-21, 1984.The binding and internalization of cholera toxin (CT) into the intestinal epithelium were studied in vivo in rats. The distribution of CT was ascertained using immunofluorescence and by immunoenzymeelectron microscopy, with horse-radish peroxidase anti-CT antibodies as the conjugate. The toxin was rapidly bound and internalized into both epithelial and goblet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…and cytochalasin B causes an immediate secretion presumably by disruption of microfilaments. W e have previously shown that cytoplasmatic CT in epithelial cells is concentrated to the terminal web region (9) supporting the idea that CT might interact directly with cytoskeletal components. However, cholera secretion seems largely to depend on CT-induced activation of adenylate cyclase located in the basolateral membrane (22).…”
Section: Db-campmentioning
confidence: 60%
See 4 more Smart Citations
“…and cytochalasin B causes an immediate secretion presumably by disruption of microfilaments. W e have previously shown that cytoplasmatic CT in epithelial cells is concentrated to the terminal web region (9) supporting the idea that CT might interact directly with cytoskeletal components. However, cholera secretion seems largely to depend on CT-induced activation of adenylate cyclase located in the basolateral membrane (22).…”
Section: Db-campmentioning
confidence: 60%
“…Liglir and rlocirotz tnicroscop. Sections for light and electron microscopic examination were prepared as previously described (9). Multiple sections from several blocks from each loop were carefully analysed in order to evaluate the significance of the structural changes observed.…”
Section: Muirriulsmentioning
confidence: 99%
See 3 more Smart Citations